Analisis Pemilihan Vendor Untuk Mendukung Overhaul Auxilary Power Unit (APU) Dengan Metode AHP Di Perusahaan Perawatan Pesawat - Albarty, Hanifa Fathiya; Torik, Torik (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
Business competition especially in the field of aircraft maintenance, price and time are the main points. In addition, capability will be an added value to attract consumers and absorb the market. Those with limited capability, usually must work with vendors to fulfill the part repair process. The company experienced a lot of delays in Turn Around Time (TAT) for the GTCP 131-9B Auzilary Power Unit (APU) project in 2019. The main problem that occurred was that APU part repaired at vendor delays, thus hampering maintenance process. To avoid the same problem, company will evaluate vendor selection to support maintain TAT on APU maintenance process. Currently, the company does not yet have an objective assessment for selecting vendors. The AHP method was chosen to solve the multi- criteria problem of selecting the best vendor according to the required criteria. In the hierarchical structure, company has five main criteria for evaluating four alternative vendors. With AHP method, it was found that the price and lead time criteria are the main priorities with a weight of 0.391 and 0.300. In addition, the best alternatives obtained vendor B with 0.443 score.